TEMA-TEMA KAJIAN AL-QUR’AN DI BARAT PERSPEKTIF FAZLUR RAHMAN (1919-1988) - Muhammad Anshori (QOF, 2020)
Western scholars have written on various themes or topics on the Qur'an so that the number of works or literature on this issue is very large. One of the Muslim scholars who carried out a mapping of the theme of al-Qur'an studies in the West was Fazlur Rahman (1919-1988). He was one of the Muslim scholars who had studied and taught in the West, so that his scientific authority was recognized by many circles. This paper aimed to analyze the typology or specific themes of al-Qur'an research in the context of literature developing in the Western world in general, especially before and during Rahman's time. Using historical analysis methods and literature criticism, Rahman mapped all literature related to the study of the Koran in the West into three main themes. First, literature or works attempted to prove that the Qur'an had been influenced by Judeo-Christian teachings. Second, literary literature examined the chronological arrangement of verses and surahs of the Koran. Third, literatures studied the Koran in general or certain topics. The discourse of the study of the Qur'an in the West cannot be separated from these three themes.